A new, high electrochemical activity and chromium tolerant cathode for solid oxide fuel cells - Zhao, L.; Cheng, Y.; Jiang, San Ping (2015)
© 2015 Hydrogen Energy Publications, LLC. The commercialization of solid oxide fuel cell (SOFC) technologies requires the development of cathode materials not only with high electrochemical activity and stability but also with excellent tolerance and resistance towards contaminants such as chromium. Here, a new electrode, Sm0.5(1-x)Sr0.5(1-x)BaxCo1-0.3xFe0.2xNb0.1xO3-d (SSBCFN with x = 0.4, 0.5, 0.6) is developed based on the combined composition of Sm0.5Sr0.5CoO3-d (SSC) and Ba(Co0.7Fe0.2Nb0.1)O3-d (BCFN). SSBCFN with x = 0.5 (SSBCFN5) shows a high electronic conductivity of 128-221 S cm-1 in the temperature range of 500-900 °C, an essential requirement of SOFCs electrode materials and low electrode polarization resistance of 0.53 ?cm2 at 600 °C, significantly lower than 1.79 ?cm2 for the reaction on SSC and 0.64 ?cm2 on BCFN. SSBCFN5 shows cubic perovskite structure with a high oxygen non-stoichiometry, d = 0.514 ± 0.027, based on chemical titration method. Compared to SSC and BCFN electrodes, SSBCFN5 shows better electrochemical activity for the oxygen reduction reaction and most importantly, it exhibits excellent stability and resistance toward chromium deposition and poisoning under SOFC operation conditions from 700 to 900 °C. The results indicate that SSBCFN5 is a promising potential cathode of SOFCs with high activity, stability and high tolerance towards contamination by Cr.